PENGARUH PENERAPAN SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA (SMK3) DAN KONDISI LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KARYAWAN DI PT. BMS KECAMATAN ANGKONA KABUPATEN LUWU TIMUR SULAWESI SELATAN: ABSTRACT - Evi Kurniasari (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2019)
Research Objectives: To determine the effect of the application of occupational safety and health (SMK3) and working environment conditions on employee productivity and determine the effect of demographic variables such as age, education, and years of service on employee work productivity. Method: This research method uses a type of survey research with a cross-sectional design, then distributes questionnaires to 81 respondents who are sampled. Sampling is done randomly according to the employee's room. Data were analyzed using statistical analysis through cross tabulation followed by chi square test and multiple linear analysis. Results: The results of this study have a significant influence on the occupational health and safety management system (SMK3) and work environment conditions on employee work productivity with a p value = 0,000 (<0.05). as for the influence of age, years of service, smk3, and the conditions of the work environment together have a significant effect on employee productivity as much as 82.5%. Then education does not significantly influence productivity because it has a p-value of 1,000 (> 0.05) so that Ho be accepted. Discussion: Occupational health and safety has a role in ensuring the safety of the production process by the workforce so that productivity can be achieved. Conclusion: The conclusion of this study shows that there is a significant effect between occupational safety and health management systems and employee productivity with a p value of 0,000 (<0.05), there is an influence on the work environment condition on productivity with a p value of 0,000, there is an influence on age productivity with a p value of 0,000, there is an influence of work period on productivity with a p value of 0,000 and there is no relationship between education and productivity with a p value of 1,000 (> 0.05). Suggestion: Management System Employee safety and health still need to be improved through employee simulations and training on SMK3 especially giving first aid during workplace accidents